2005
DOI: 10.1007/s00170-004-2057-z
|View full text |Cite
|
Sign up to set email alerts
|

A simulated investigation on the machining instability and dynamic surface generation

Abstract: Abstract:In this paper, the authors propose the generic concept of machining instability based on the analysis of all kinds of machining instable behaviors and their features. The investigation covers all aspects of the machining process, including the machine tool structural response, cutting process variables, tooling geometry and workpiece material property in a full dynamic scenario. The paper presents a novel approach for coping with the sophisticated machining instability and enabling better understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Thus, in order to understand the machine tool dynamics and influence of cutting parameters on chatter, various mathematical models have been developed. In this regard, a comprehensive study has been done by Luo et al [2]. In their work, they proposed a novel modelling approach and simulation * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in order to understand the machine tool dynamics and influence of cutting parameters on chatter, various mathematical models have been developed. In this regard, a comprehensive study has been done by Luo et al [2]. In their work, they proposed a novel modelling approach and simulation * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the chatter problem of metal materials, many scholars [1][2][3][4][5][6][7][8][9][10][11][12][13] have conducted studies and found that chatter is often generated by three factors, i.e., ripple regeneration, mode coupling, and friction. In the study of ripple regeneration (which is caused by surface ripples), Luo et al [14] adopted a hybrid digital method to solve the problem of surface ripple regeneration. Altintas and Weck [15] studied the stability of regenerative chatter during metal cutting.…”
Section: Introductionmentioning
confidence: 99%
“…For decades, surface generation modeling and experiment under the influence of related factors attracts lots of attention [7][8][9][10][11]. In ultra-precision flycutting, the machined surface is also affected by the above mentioned factors, and many related researches can be found.…”
Section: Introductionmentioning
confidence: 99%